P-178 Can we give dying hospital patients better care?. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Thomas, Keri; Wilson, Julie Armstrong; Clifford, Collette
Abstract : Aims: A third of hospital patients are in their last year of life, almost 50% of people die in hospital, and most do not die where they choose. Poor end of life care in UK hospitals has received much recent attention and is recognised as a key area for improvement. With earlier recognition and a more proactive approach, more might receive better care, be discharged home earlier, with fewer hospital deaths. The Gold Standards Framework (GSF) is a quality improvement programme delivering proactive person-centred population-based care for people in the last years of life in all settings. We report on the introduction and impact of the first eight years of the GSF Acute Hospitals Programme, with findings from the first GSF Accredited wards. Method: The structured two- year GSF Hospital training programme includes training, tools, support and evaluation at organisational, patient and staff level, including measures of progress and attainment and some independent evaluations. GSF encourages teams to identify patients earlier (aiming for the 30% figure where appropriate), assess their needs (offering all initial advance care planning discussions) and proactively planning care aligned to preferences, enabling more to die at home. Results: Evaluations indicate significant progress in several key areas in many hospitals and a 'culture change' on the wards. GSF Accredited wards show embedded good practice including earlier identification (average 35%), more proactive needs-based approach, more offered advance care planning discussions (75%–95%), better communication with GPs, reduced hospitalisation and improved more appropriate referrals to palliative care specialists. Conclusions: Findings from the first phases of GSF trained hospitals and the first accredited wards show significant changes, with proactive, better coordinated, person-centred care. A key factor is earlier recognition which is increasingly being attained.